Larval Debridement Therapy for Management of Postsurgical Wounds in the Setting of Pyoderma Gangrenosum - Wayne B. Bauerle, MD; Jacqueline M. O’Connell, PA-C; Olivia Hoy, BS; Muller Pierre-Louis, MD; Daniel Eyvazzadeh, MD; Christopher Sanders, MD; Laura Huang, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Pyoderma gangrenosum (PG) is a rare disease affecting 5.8 adults per 100,000 in the United States. PG is not exclusively seen in inflammatory bowel disease; however, among those with inflammatory bowel disease, upward of 0.4%–2% may have concomitant PG. Wounds in the setting of PG are a challenge for clinicians to treat, especially when refractory to first-line agents such as immunosuppressive agents and biologic therapy. Herein, we present the case of a patient with PG who underwent a colostomy reversal, developed a PG wound, and was successfully treated with larval debridement therapy (LDT). A 62-year-old man underwent elective reversal of his loop sigmoid colostomy. He had developed an anastomotic leak, requiring a descending colostomy and mesh removal. Ultimately, he developed a pyoderma wound at the previous ostomy site. Cyclosporine, prednisone, antibiotics, dressing changes, a single debridement, and biologic therapy failed to heal the wound. After 2 applications of LDT, the wound healed completely. Literature regarding LDT for nonhealing diabetic wounds and pressure ulcers is well described; however, its use for abdominal wounds in the setting of PG is not well documented. Most case reports on LDT for abdominal wounds discuss only a partial response with minimal to no wound healing. Unlike the previously published literature, our case report demonstrated complete wound response without decreased larvae survivability in the setting of previously administered immunosuppressants. LDT appears to be a viable option for patients who do not appropriately respond to first-line medical therapies for surgical wounds in the setting of PG.